Tradition of arranged marriage among Bugis girls in Mendahara Ulu - Ariani, Zeni Ayu (Jurnal Anifa: Studi Gender dan Anak, 2025)
The practice of arranged marriage involving young girls in the Bugis community of Mendahara Ulu reflects a complex intersection between cultural authority and religious values. This study explores the mechanisms of power embedded in Bugis arranged marriage traditions by applying Michel Foucault’s theory of power relations in conjunction with Islamic ethical principles. Employing a qualitative case study approach, the research involved Bugis women who had experienced arranged marriages. Data were collected through in-depth interviews and a literature review, then analyzed using critical discourse analysis. The findings reveal that arranged marriage functions not solely as a cultural norm but as a contested arena of power among parents, customary practices, and the women themselves. Key Islamic principles—such as gender justice and mutual consent—are often marginalized or narrowly interpreted. The study argues for a more integrative approach that harmonizes local customs with Islamic values to promote women’s rights and agency. This research offers a nuanced perspective on how cultural and religious discourses shape the practice of arranged marriage in contemporary Muslim contexts.